A possibility of photonuclear production of planar ¹⁷⁹Tа sources - Dikiy, N.P.; Lyashko, Yu.V.; Rogov, Yu.V.; Uvarov, V.L. (Вопросы атомной науки и техники, 2013)
Age-specific reduction of the bone mass (osteoporosis) is one of the most progressing human illness throughout the world. Its diagnostic is based on a measurement of the mineral density of bone mass by radiation absorptiometry technique. In the communication, a possibility to use gamma-sources on the basis of the ¹⁷⁹Tа isotope for osteoporosis diagnostics is considered. The isotope can be produced by the ¹⁸¹Ta(γ, 2n)¹⁷⁹Tа reaction in a high-energy X-ray radiation field using a target from natural tantalum. Conditions of the ¹⁷⁹Tа planar sources production at an electron accelerator were studied. By computer simulation, an optimization of target geometry has been conducted. Yield of target isotope and admixtures have been measured at a bremsstrahlung end-point energy of 40 MeV. Вікове зниження кісткової маси (остеопороз) є одним з найбільш прогресуючих видів захворювань у світі. Його діагностика заснована на вимірюванні мінеральної щільності кісткової маси методами променевої абсорбціометрії. Розглянута можливість використання для діагностики остеопорозу гамма-джерел на основі ізотопу ¹⁷⁹Tа (ЕХ~54 кeВ; Т₁/₂=665 днів). Його можна напрацьовувати в полі високоенергетичного гальмівного випромінювання за реакцією ¹⁸¹Ta(γ, 2n)¹⁷⁹Tа у мішені з природного танталу. Досліджено умови отримання планарних джерел ¹⁷⁹Tа на прискорювачі електронів. Методом комп'ютерного моделювання проведена оптимізація геометрії мішеневого пристрою. Виміряні виходи цільового ізотопу і домішок при граничній енергії гальмівного випромінювання 40 МеВ. Возрастное снижение костной массы (остеопороз) является одним из наиболее прогрессирующих видов заболеваний в мире. Его диагностика основана на измерении минеральной плотности костной массы методами лучевой абсорбциометрии. Рассмотрена возможность использования для диагностики остеопороза гамма-источников на основе изотопа ¹⁷⁹Tа (ЕХ~54 кeВ; Т₁/₂=665 дней). Его можно производить в поле высокоэнергетического тормозного излучения по реакции ¹⁸¹Ta(γ, 2n)¹⁷⁹Tа в мишени из природного тантала. Исследованы условия получения планарных источников ¹⁷⁹Tа на ускорителе электронов. Методом компьютерного моделирования проведена оптимизация геометрии мишенного устройства. Измерены выходы целевого изотопа и примесей при граничной энергии тормозного излучения 40 МэВ.